Improved miscibility of PA6 and chitosan by the electric-field assisted phase inversion. (1st June 2018) - Zhang, Jingjing; Zhou, Qi; Li, Wei; Petrov, Oleg; Mattea, Carlos; Stapf, Siegfried
Graphical abstract: Highlights: Miscibility of chitosan and polyamide is improved by the presence of electric field. Electric field orients the polar groups, adjusting the hydrogen bonding of blends. Toughness and tensile strength of blends both increase owing to the electric field. Abstract: A facile and efficient method for the improved miscibility of natural polymer/synthetic polymer blends is reported here based on the electric-field-driven phase inversion. We have employed bioderived chitosan (CS) and Polyamide-6 (PA6) as an example since their blends are known to always result in a large scale phase separation ( i.e. CS settles to the bottom of the blends as sediment) during phase inversion procedure. The condensed structure of the polymer blends has been well characterized, notably by the polarized attenuated total reflectance infrared spectroscopy and proton longitudinal relaxation time ( T1 ) distribution. The application of an electric field can orient the polar groups which will hinder the crystallization of blends and also increase the interphase interaction between PA6 and CS. The miscibility of the PA6/CS blends has been characterized by scanning electron microscopy and confocal Raman spectroscopy. It is shown that this controllable hydrogen bonding environment, induced by the presence of electric field, indeed greatly hinder the sedimentation of CS without destroying its chemical structure. The improved miscibility of PA6/CS blends can thus significantly increase the toughness and generate a somewhat larger tensile strength.